The Phenomenon Of Sadbor Dance On Tiktok: Farmers' Weak Weapon In The Spiral Of Silence And Daily Resistance - Abdul Rahman Matondang; Syukur Kholil (Journal of Research in Social Science and Humanities, 2024)
The Sadbor dance phenomenon on TikTok shows how Indonesian farmers use social media as a survival strategy amid economic constraints. This trend emerged amidst a difficult economic situation, where many farmers were forced to seek additional income through digital platforms. This study aims to understand the Sadbor dance as a form of everyday resistance in the context of James Scott's theory and as a response to the Spiral of Silence by Elisabeth Noelle-Neumann. The novelty of this study lies in the effort to connect the socio-economic phenomenon of farmers with the theory of symbolic resistance in the digital era. This study uses a qualitative method with content analysis of the Sadbor dance video and public responses. The results show that the Sadbor dance is not just entertainment, but also a hidden medium of expression that reflects farmers' dissatisfaction with unfair economic conditions. The recommendation of this study is the need for more attention from the government to the welfare of farmers through stronger economic support, so that they have alternatives outside of social media to improve their standard of living.